Investigation of the correlation of academic motivation and music performance anxiety levels - MALKOÇ, TÜLÜN (My University, 2020)
This research was carried out to measure the academic motivation levels of  pre-service music teachers as well as the  music performance anxiety levels to investigate potential correlations between them. The sample group of this scanning modelled study is comprised of 241 students studying at departments of music education at Niğde Ömer Halis Demir University, Pamukkale University, Konya Necmettin Erbakan University and Karadeniz Technical University. To determine the demographic features of the students taking part in the study, a demographic information form was used. In order to measure students’ music performance anxiety and academic motivation levels, the data collected using the Music Performance Anxiety Scale and Academic Motivation Scale. The data was analyzed using percentage and frequency distributions. The Pearson Product Moments’ Correlation technique, which is commonly used to calculate the correlation between the variables, was used. As the result of the findings obtained from the study, a significant positive correlation was found between music performance anxiety and academic motivation levels of the students. The anxiety and academic motivation levels of pre-service teachers were found to be moderate.   Keywords: Music education; music teacher, music performance anxiety, academic motivation.